Remogliflozin Etabonate in the Treatment of Type 2 Diabetes: Design, Development, and Place in Therapy - Mohan V; Mithal A; Joshi SR; Aravind SR; Chowdhury S (Dove Medical Press, 2020)
Viswanathan Mohan,1 Ambrish Mithal,2 Shashank R Joshi,3 SR Aravind,4 Subhankar Chowdhury5 1Madras Diabetes Research Foundation & Dr. Mohan’s Diabetes Specialties Centre, Chennai, Tamil Nadu, India; 2Endocrinology and Diabetology, Max Healthcare Hospital, Gurgaon, India; 3Joshi Clinic, Lilavati Hospital, Apollo Sugar Clinic and Bhatia Hospital, Mumbai, India; 4Diacon Hospital, Bengaluru, India; 5Deptartment of Endocrinology, IPGME&R and SSKM Hospital, Kolkata, IndiaCorrespondence: Viswanathan Mohan Tel +91 44 4396 8888Fax +91 44 2835 0935Email drmohans@diabetes.ind.inAbstract: Type 2 diabetes mellitus (T2DM) is an emerging epidemic in Asian countries, especially in India. With the advent of the SGLT2 inhibitor class of drugs demonstrating benefits beyond glycemic control, viz. weight loss, blood pressure reduction, and cardiovascular and renal protection, the management of T2DM has taken a quantum leap. Remogliflozin etabonate (RE) is the latest addition to the SGLT2 inhibitor class of drugs that have been recently approved in India for the management of T2DM. RE is a potent and selective inhibitor of SGLT2 with the unique distinction of being administered as a prodrug, existence of active metabolites, and short half-life necessitating twice-daily dosing. The Phase III study of RE demonstrated it to be an efficacious and safe agent and non-inferior to the currently available SGLT2 inhibitors. This paper reviews not only the pharmacokinetics, pharmacodynamics, clinical efficacy, and safety profile of RE but also its molecular and clinical development program. This review has taken into consideration all available published as well as unpublished literature on RE and discusses the individual studies performed during its development for characterization of pharmacological profile.Keywords: remogliflozin, etabonate, SGLT2 inhibitor, design, development, place in therapy, T2DM